African Continental Free Trade Area Agreement (Afcfta) And the Challenges of Regional Integration in Africa - Olileanya Amuche Ezugwu; Moses, M. Duruji (International Journal of Social Service and Research, 2023)
The African Continental Free Trade Area Agreement (AfCFTA) represents a significant milestone in Africa's pursuit of regional integration and economic development. Envisioned as a pan-African initiative, the AfCFTA aims to establish a single market for goods and services, promote intra-African trade, and foster economic growth across the continent. This paper examines the challenges of regional integration in Africa and explores the potential benefits of the AfCFTA Agreement in addressing these challenges. This study uses qualitative research methods, with secondary data from scholarly publications, journal articles, reports from international organisations, and literature studies that were thematically analysed. The study results show that disparities in economic development and industrial capacities among African nations, persistent trade barriers, non-tariff obstacles, weak institutional frameworks, the paradox of sovereignty, and inadequate infrastructure primarily drive the challenges of African integration. The study also reveals that adopting the AfCFTA Agreement in 2019 has brought more African nations involved in addressing these economic integration challenges and fostering deep cooperation within the continent. This paper concludes that the AfCFTA Agreement has the potential to be a transformative force in advancing regional integration and economic prosperity in Africa. However, a pragmatic approach is continually needed to address these integration challenges. This paper thus recommends fostering inclusive growth and economic diversification through targeted policies that can address economic disparities among African nations. Also, it emphasises the inclusion of marginalised sectors, such as small and medium-sized enterprises (SMEs) and informal traders, which is essential for maximising the AfCFTA's potential benefits and fostering sustainable economic growth.